Thousand letters method (Journal of Parents and Teachers, 2014)
We stand before the eternal debate, the ever burning question: at what age should children learn to read? In this article of Parents and Teachers the MIL lyrics method is presented, based on the own experience of a school that teaches reading and writing in the last year of Infant Education. The method is synthetic and phonetic, and is that the phoneme-grapheme association is made by drawing the letters as an object or animal that the child recognizes.
Keywords: literacy; reading; writing; teaching; drawings.